Memory and the Future Transnational Politics, Ethics and Society - Gutman, Yifat; Brown, Adam D.; Sodaro, Amy.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
For those who study memory, there is a nagging concern that memory studies are inherently backward-looking, and that memory itself hinders efforts to move forward. Unhinging memory from the past, this book brings together an interdisciplinary group of prominent scholars who bring the future into the study of memory.
Keywords: Civilization—History.; Culture—Study and teaching; Culture; Human rights; Social history; Education; Cultural History; Cultural and Media Studies, general; Sociology of Culture; Human Rights; Social History; Popular Science in Education